PROFIL LULUSAN FAKULTAS TEKNIK BERDASARKAN ASAL SEKOLAH DAN JALUR - SUGIYONO SUGIYONO (Jurnal Kependidikan, 2002)
Abstract This study was aimed at finding out the aptitude profile of the graduates of the Faculty of Engineering of the State University of Yogyakarta. The subjects were the students graduated from the faculty in academic years 1995 up to 2001. The total number of subjects was 1276. The students were classified based on their education background and their entrance selected system. There are two kinds of educational background, namely SMU (general High School) and SMK (Vocational High School) . there are also two kinds of entrance selection system, namely UMPTN (National Entrance Examination) and PBU (Talent Scouting System). The following results have been identified. (1) The mean of the GPA’s of the students of the SMK-PBU group (2.85) is higher than that of the students of the SMU-UMPTN group (2.77). (2) The length of study and the age of student have negative correlation with GPA. (3) All the best ten students of the SMK-PBU group. (4) Of the students in the “skripsi” stream there are more students of the SML group (33%) than the students of the SMU group (31%). Keywords: aptitude profiles, entrance examination, and student talent scouting system